Masyarakat Adat dan Toba PULP Lestari: Pemetaan Aktor dan Analisis Konflik Agraria - Alfian, Alfian; Kudussisara, Kudussisara; Maimunah, Nur Siti; Susana, Ida (Department of Anthropology, 2025)
This study examines the agricultural disputes involving the Batak Toba population in Pandumaan and Sipituhuta Village within the Pollung District of Humbang Hasundutan Regency, North Sumatra. The dispute occurs between the indigenous populations and PT. Toba Pulp Lestari, chiefly because the company's activities infringe upon the traditional territories of the local community. The research approaches involved collecting literature and pertinent sources to correctly represent actual happenings in the field. The research seeks to identify the principal participants in the conflict and examine its fundamental dynamics. Research reveals that the violence was caused by overlapping land claims between the Pandumaan-Sipituhuta indigenous community and PT. Toba Pulp Lestari. The problem is exacerbated by the government-sanctioned concession of property to the firm, which immediately overlaps with the territories historically inhabited by the indigenous population. The principal stakeholders in this dispute comprise the indigenous communities, the corporation, federal and local government agencies, security forces, NGOs, and the media, which significantly influences the reporting of these developments.Abstrak: Penelitian ini mengkaji konflik agraria di antara masyarakat Batak Toba yang berada di Desa Pandumaan dan Desa Sipituhuta, Kec Pollung, Kab Humbang Hasundutan, Sumatera Utara. Konflik antara masyarakat adat dan PT. Toba Pulp Lestari yang menjamah wilayah adat dari masyarakat adat tersebut. Penelitian ini dilakukan dengan mengumpulkan literatur dan bacaan terkait, guna memperoleh kejadian real di lapangan. Penelitian ini bertujuan untuk memetakan aktor yang terlibat dalam konflik dan juga menganalisis konflik yang terjadi. Hasil penelitian menyebutkan bahwa konflik yang terjadi dipicu oleh tumpang tindih penguasaan lahan oleh masyarakat adat Pandumaan-Sipituhuta dengan PT. PTL. Hal ini dikarenakan wilayah konsensi perusahaan yang diberikan kuasa oleh pemerintah bersinggungan dengan wilayah adat yang ditempati oleh masyarakat. Aktor yang terlibat dalam konflik ini antara lain adalah masyarakat adat, perusahaan, pemerintah pusat dan daerah, aparat keamanan, dan LSM, serta media sebagai pihak luar yang turut memberitakan konflik tersebut.